Inovasi Nugget Sayur Untuk Pencegahan Stunting Balita Oleh Mahasiswa Kukerta UNRI - Fitrilinda, Dafetta; Pratama, M. Raditya Ditto; Wahyuni, Sri; Kartini, Putri Dwi; Selvia, Ayu; Yuniorda, Kingpen Tresia; Azzahra, Fatimah; Ramadani, Novreiza; Hanum, Khairunnisa Latiffah; Al Khairi, M. Habib; Adikasa, Yoel (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2023)
Alampanjang Village, Rumbio Jaya District, Kampar, Indonesia is an area with a population of around 3,362 people, who earn their living as farmers and employees. This village does not have high stunting data, however, the village and sub-district governments are still making efforts to prevent stunting. For this reason, the government has created a program to prevent stunting in toddlers through community service activities carried out by Riau University students who undertake Real Work Lectures (Kukerta) in Alampanjang Village. The program carried out is the creation of innovative vegetable nuggets and is carried out together with Mrs. PKK Alampanjang Village, precisely in V Torok Hamlet. The aim of this program is the first step in preventing stunting which can be done easily by the mothers of Alampanjang Village in their homes and can be used as an idea for MSMEs. The method used is to use participatory methods through socialization and direct practice in making vegetable nugget innovations. In order to achieve this, an educational video has been made on the Kukerta YouTube page as well as the importance of public understanding about stunting prevention as evidenced by the very enthusiastic response from the public in participating in the program.